Effects of dopamine on retinal and choroidal blood flow parameters in humans. Issue 9 (23rd March 2007) - Huemer, Karl-Heinz; Zawinka, Claudia; Garhöfer, Gerhard; Golestani, Elisabeth; Litschauer, Brigitte; Dorner, Guido T; Schmetterer, Leopold
Abstract : Aim: To investigate the effect of dopamine on retinal and choroidal blood flow in humans. Methods: We investigated the effect of two doses of intravenous dopamine (5 and 10 µg/kg/min) via a randomised double-masked crossover study in 12 healthy subjects chosen from a total of 16. Blood flow parameters in retina, optic nerve head and choroid were assessed with bi-directional laser Doppler velocimetry, laser Doppler flowmetry and laser interferometric measurement of fundus pulsation amplitude, respectively. Results: Intravenous dopamine dose-dependently increased retinal blood cell velocity and fundus pulsation amplitude (p<0.001). At the highest administered dose red blood cell velocity in retinal vessels increased by 37% and fundus pulsation amplitude by 24%. By contrast, optic nerve head blood flow did not change with dopamine administration. Conclusions: Our data indicate that dopamine has a pronounced enhancing effect on the retinal perfusion in humans. Further studies are required to establish the exact role of dopamine in the regulation of choroidal and optic nerve head blood flow.